Implementasi Open Source Intelligence dalam Praktik Jurnalisme di Media Online - Haris Wahyudi; Arba'iyah Satriani (Bandung Conference Series: Journalism, 2023)
Abstract. OSINT, as defined by the Army's Headquarters Department, is an intelligence activity that seeks to gather, exploit, and disseminate information obtained from open sources in order to discover specific information. However, the implementation can be carried out at any location. In Indonesia itself, the possibility of OSINT really turned into a subject of discussion in 2004. Even Kominfo organized the Indonesia Open Source Award event in 2012 (IOSA 2012). However, until now, it has only been used sparingly. In the domain of news coverage in Indonesia, this is additionally still seldom finished by the media. As a result, the researcher wants to learn how OSINT is used in Detikcom's online media by using the Cimahi child murder case as an example. This research employs a case study-based qualitative approach. There are two types of data collection methods, primary collection: Observation, Interview, Literature Study, Internet Sources, and additional secondary data collection: Documentation Additionally, representatives from the Press Council and Detikcom's editors and assistant editors served as informants for this study. The goal of this study is to learn how OSINT is used in online media. The online media outlet Detik.com served as the subject of this investigation, and DetikCom's coverage of the murder of children in Cimahi served as the object. The researcher will speak with Press Council representatives as part of the data triangulation process. Abstrak. Menurut Headquarters Department of the Army, OSINT merupakan sebuah kegiatan intelejen yang bertujuan untuk mengetahui informasi tertentu dengan cara mengumpulkan, mengeksploitasi, dan menyebarluaskan sebuah informasi yang didapat dari sumber terbuka. Meski begitu, Implementasinya bisa dilakukan dimana saja. Di Indonesia sendiri, gagasan mengenai OSINT sebenarnya sudah menjadi perbincangan pada 2004. Bahkan pada 2012, Kominfo sempat menggelar perhelatan Indonesia Open Source Award (IOSA 2012). Namun sampai saat ini penggunaannya masih dirasa minim. Dalam ranah jurnalisme di Indonesia, hal ini juga masih terhitung jarang dilakukan oleh media. Oleh karena itu peneliti ingin mempelajari bagaimana OSINT digunakan di media online Detikcom dan pengaruhnya terhadap jumlah pembaca dengan mengambil contoh kasus pembunuhan anak di Cimahi. Penelitian ini menggunakan pendekatan kualitatif berbasis studi kasus. Ada dua jenis metode pengumpulan data, pengumpulan primer: Observasi, Wawancara, Studi Literatur, Sumber Internet, dan pengumpulan data sekunder tambahan: Dokumentasi. Selain itu, perwakilan dari Dewan Pers dan redaktur Detikcom serta asisten redaktur menjadi narasumber dalam penelitian ini. Tujuan dari penelitian ini adalah untuk mempelajari bagaimana OSINT digunakan dalam media online dan pengaruhnya terhadap jumlah pembaca. Media online Detik.com menjadi subjek investigasi ini, dan liputan DetikCom tentang pembunuhan anak di Cimahi menjadi objeknya.